Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening Pada Rumah Sakit Dr. Reksodiwiryo Padang - Finola, Finola; Yulasmi, Yulasmi; Bayu Pratama Azka (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The influence of reward and punishment on employee performance through work discipline as an intervening variable at dr. Hospital. Reksodiwiryo Padang City "under the guidance of dr. YULASMI, SE, MM and Mr. BAYU PRATAMA AZKA, SE, MM This research aims to test how big the influence of rewards and punishment is on employee performance with work discipline as an intervening variable at dr. Reksodiwiryo Hospital, Padang city. The sample in this study amounted to 53 respondents. This population is employees at dr. Reksodiwiryo Hospital. As times progress in the current era of globalization, rivalry and competition are becoming increasingly tighter and wider. Because of this, all human resource potential influences the organization's efforts to achieve its goals. Work discipline can be enforced by providing rewards and punishment. This research aims to determine the direct and indirect influence of reward and punishment on employee performance with work discipline as an intervening variable.This research uses quantitative research, which emphasizes testing theories on variables in the research with numbers and analysis. The measuring tool for this research is a questionnaire. The objects of this research were employees of dr. Reksodiwiryo Hospital with a sample of 53 respondents. The sample determination method used was simple random sampling. The data analysis test tool in this research is Smart PLS. The research results show that reward and punishment do not have a direct influence on employee performance. Meanwhile, there is an indirect influence of reward and punishment variables on employee performance through work discipline.